KUALITAS PRODUK, PEOPLE DAN KELOMPOK RUJUKAN TERHADAP MINAT BELI ULANG PADA MERY BEAUTY STUDIO KOTA SUNGAI PENUH - Melifia Liantifa; Anggia Ayu Lestari; Violin Alfa Lahesa (Jurnal Ekonomi Sakti, 2023)
This study aims to determine the effect of product quality, people and reference group on the repurchase interest at the Mery Beauty Studio, Sungai Penuh City. The sample of this study were 80 customers of Mery Beauty Studio. Collecting data using a questionnaire method. The data analysis tools used are Descriptive Analysis, Multiple Linear Regression, Coefficient of Determination and the hypothesis test used is the t-test and F-test. The results of the product quality research have significant effect on Repurchase Interest at Mery Beauty Studio, this is evidenced with a significance value 0,003 < 0.05. People do not have significant effect on Repurchase Interest at the Mery Beauty Studio, this is evidenced with a significant value 0.495 > 0.05. The Reference Group had no significant effect on Repurchase Interest at Mery Beauty Studio, this was evidenced with a significance value 0.150 > 0.05. Simultaneously there is a significant influence between product quality, people and reference group on interest in repurchasing at the Mery Beauty Studio, which can be proven by the value significance 0.018 < 0.05 with a large effect of 31.61%.